2020
DOI: 10.1212/nxg.0000000000000523
|View full text |Cite
|
Sign up to set email alerts
|

The SPID-GBA study

Abstract: ObjectiveTo provide a variant-specific estimate of incidence, penetrance, sex distribution, and association with dementia of the 4 most common Parkinson disease (PD)-associated GBA variants, we analyzed a large cohort of 4,923 Italian unrelated patients with primary degenerative parkinsonism (including 3,832 PD) enrolled in a single tertiary care center and 7,757 ethnically matched controls.MethodsThe p.E326K, p.T369M, p.N370S, and p.L444P variants were screened using an allele-specific multiplexed PCR approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…When stratified by variant, in one study, PD carriers of severe or biallelic variants showed worse cognitive function compared with noncarriers, whereas mild or risk variants did not ( 30 ). However, other studies found that risk variants (p.E326K) were associated with similar cognitive deterioration ( 26 , 48 ), or faster progression to dementia compared with pathogenic GBA variants ( 49 , 50 ), as opposed to what is expected on the basis of the impact on GCase activity.…”
Section: Genotype–phenotype Correlation With Clinical Profile In Gba -Parkinson Diseasementioning
confidence: 87%
“…When stratified by variant, in one study, PD carriers of severe or biallelic variants showed worse cognitive function compared with noncarriers, whereas mild or risk variants did not ( 30 ). However, other studies found that risk variants (p.E326K) were associated with similar cognitive deterioration ( 26 , 48 ), or faster progression to dementia compared with pathogenic GBA variants ( 49 , 50 ), as opposed to what is expected on the basis of the impact on GCase activity.…”
Section: Genotype–phenotype Correlation With Clinical Profile In Gba -Parkinson Diseasementioning
confidence: 87%
“…Heterozygous GBA mutations are currently recognized as the most frequent genetic risk factor for PD [ 182 , 183 ], with a three-fold higher risk of developing PD dementia (PDD) and Dementia with Lewy Bodies (DLB) [ 184 , 185 , 186 , 187 ]. It is estimated that 5–10% of PD patients are carriers of GBA mutations worldwide (Odds Ratio: 3–4.7 for mild mutations, 14.6–19.3 for severe mutations [ 187 ]) [ 182 , 184 ], with even higher prevalence rates in specific ancestries [ 188 ]. Four missense GBA variations (p.E326K, p.T369M, p.N370S, and p.L444P) account for almost 82% of all mutant alleles found in PD [ 189 ].…”
Section: Autosomal Dominant Genes With Variable Penetrancementioning
confidence: 99%
“…Genetic alterations and mutations in familial PD forms, such as SNCA, Parkin, LRRK2, DJ-1, PINK-1, and UCHL-1, only account for approximately 10% of idiopathic PD patients. Age of onset and clinical symptoms are variable, as example convincingly demonstrated in Glucocerebrosidase (GBA) mutation carriers [ 104 , 105 , 106 , 107 , 108 ]. Neuroprotection trials are again under way in these GBA mutation carrying PD patients.…”
Section: Parkinson’s Diseasementioning
confidence: 99%